Analysis of Community-Based Tourism Potential and Management Strategies for the Destination of Community Care Tourism in Kedung Sahong Ciliwung - Mularsari, Ardi; Nugraha, Rizki Nurul; Pratiwi, Rahmadiani (Westscience Press, 2024)
This research discusses the potential of community-based tourism and management strategies for the Komunitas Peduli Ciliwung Kedung Sahong (KPC Kedung Sahong) tourist destination. The destination was established during the COVID-19 pandemic and focuses on environmental conservation, community empowerment, and sustainable services to tourists. Despite achieving significant progress, challenges such as the lack of facilities and government support persist. The research aims to understand the participation of the local community in destination development, environmental sustainability, and local economic empowerment. The concept of potential for community-based tourism is applied in developing the KPC Kedung Sahong tourist destination in South Jakarta. The potential includes local resources, tourist attraction development, community participation, and sustainable improvement and development. Community-based tourism allows active participation of the local community in destination management and development. The research uses a qualitative method with a SWOT approach to evaluate destination development's strengths, weaknesses, opportunities, and threats. The article discusses the implementation of Community Based Tourism (CBT) in the KPC Kedung Sahong Tourist Destination in South Jakarta, emphasizing the involvement of the local community. The research also highlights the importance of periodic evaluations to ensure the sustainability and success of the community-based tourism concept. The article also includes a SWOT analysis to evaluate the strengths, weaknesses, opportunities, and threats in destination development